Erzählte Ordnungen - Ordnungen des Erzählens : Studien Zu Texten Vom Mittelalter Bis Zur Frühen Neuzeit. - Fuhrmann, Daniela; Selmayr, Pia. (Berlin/Boston : Walter de Gruyter GmbH, 2021)
The series in German medieval studies includes central topics of current research debates in medieval studies and provides a place for groundbreaking research in the subject literature. The series is intended to give international and young researchers/research teams the possibility to effectively present innovative surveys and discussions to the scientific community. The series sees itself as a 'young' research forum with a high standard of quality and is therefore also open to excellent degree theses, should they enhance the series.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books